Feasibility of a High-Dose Inhaled Indomethacin Dry Powder with Dual Deposition for Pulmonary and Oral Delivery - Jamie E. Spahn; Amr Hefnawy; Feng Zhang; Hugh D. C. Smyth (MDPI AG, 2024)
In this study we have developed a high-dose dry powder inhaler formulation of indomethacin using a novel approach to carrier-based formulations. Specifically, larger drug particles serve as the carrier for the smaller micronized drug particles, such that an inhaled dose is combined with an oral dose. To study this system, the aerosol performance of a standard indomethacin-lactose formulation was compared to carrier-free micronized indomethacin and a drug-as-carrier formulation (a micronized indomethacin-coarse indomethacin blend). Indomethacin with lactose showed a very poor aerosol performance, indicating high adhesion between the drug and carrier. The performance of the carrier-free micronized drug was significantly better, indicating low cohesion. Coarse drug particles as a carrier allowed improved powder flow and aerosol performance while also providing a potential secondary route of absorption of indomethacin, namely oral. An optimal formulation ratio of 1:1 (w/w) fine indomethacin-coarse indomethacin was developed in this study.